Estimating Nitrogen Discharge in Water Exchange Regimes for Super-Intensive Shrimp Farming Systems Using Nitrogen Dynamics Model - Thi Thu Thao Nguyen (Journal of Technical Education Science, 2025)
The purpose of this study is to estimate nitrogen components and the amount of nitrogen in effluents from two super-intensive shrimp farming scenarios in Ca Mau province using the nitrogen dynamical model. The scenarios included 20% and 50% water exchange regimes at daily (a) and 15-day intervals (b) across the 90-day crop cycle. The study found that concentrations of TAN, NOx, and dissolved nitrogen increased throughout the farming cycle under a daily water exchange system. These concentrations were interrupted during periodic water changes, resulting in a considerable reduction in the nitrogen concentration in the sediment. The total nitrogen emitted from scenario (a) was ten times that of scenario (b). Periodic water replacement in scenario (b) reduced N discharge more effectively than daily water exchange in scenario (a). More than 50% replacement would result in a nitrogen content discharge that was twice as high as 20%. Thus, reducing water exchange reduces the environmental strain.